Two different pore architectures of cyamelurate-based metal–organic frameworks for highly selective CO2 capture under ambient conditions. Issue 3 (5th January 2023) - Essalhi, Mohamed; Mohan, Midhun; Dissem, Nour; Ferhi, Najmedinne; Abidi, Adela; Maris, Thierry; Duong, Adam
Abstract : Tailoring pore size and surface chemistry of MOFs for efficient CO2 capture and separation. Abstract : In the context of porous coordination materials toward CO2 capture and separation, two new metal–organic frameworks termed IRH-6 and IRH-7 were synthesized with square and rhombic microchannel pores, respectively. These materials exhibit high CO2 uptakes of 2.67 mol kg −1 (IRH-6 ) and 2.78 mol kg −1 (IRH-7 ) at 100 kPa and 298 K. Grand canonical Monte Carlo simulation demonstrated strong non-covalent interactions between quadripolar CO2 molecules and these nitrogen-rich frameworks. CO2 /CH4 (50 : 50), CO2 /N2 (15 : 85), and CO2 /H2 (15 : 85) gas mixtures were investigated by ideal adsorbed solution theory and showed excellent CO2 selectivity under ambient conditions for both porous materials. In particular, a remarkable increase in the CO2 selectivity to 102 for IRH-7 over 31 for IRH-6 was observed for the CO2 /CH4 binary mixture, which highlights the effect of pore aperture modification on preferential CO2 uptake over other conventional gases.